Respondent behavior in panel studies : a case study for income-nonresponse by means of the German Socio-Economic Panel (GSOEP) - Jörg-Peter Schräpler (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
Many validation studies deal with item-nonresponse and measurement error in earnings data. In this paper we explore motives of respondents for the failure to reveal earnings using the German Socio-Economic Panel (GSOEP). GSOEP collects socio-economic information of private households in the Federal Republic of Germany. We explain the evolution of income-nonresponse in the GSOEP and demonstrate the importance of a discrimination between refusing the income-statement or don't know.
Keywords: C81; 330; Respondent behavior; Interviewer effects; Item-Nonresponse; Panel analysis; Multilevel modeling; Interview; Meinungsforschung; Panel; Schätzung; Deutschland